A comparison of the Truview PCD and the GlideScope Cobalt AVL video‐laryngoscopes to the Miller blade for successfully intubating manikins simulating normal and difficult pediatric airways. Issue 6 (16th April 2016) - Hippard, Helena K.; Kalyani, Govindan; Olutoye, Olutoyin A.; Mann, David G.; Watcha, Mehernoor F.
Summary: Background: Video‐laryngoscopes provide better glottic visualization, but tracheal intubation times are longer, compared to conventional direct laryngoscopy in adult patients with normal airways. The objective of this randomized crossover study was to compare times to successful tracheal intubation with video‐laryngoscope and direct laryngoscopy in manikins simulating infants with normal and abnormal airways. Methods: Thirty experienced pediatric anesthesia practitioners performed tracheal intubation in three distinct manikins simulating infants with (i) a normal airway (ii), an anterior larynx, and (iii) the Pierre Robin sequence anatomy. These were performed using a standard Miller #1 blade, the GlideScope Cobalt AVL, and the Truview PCD video‐laryngoscope, first in a normal neck and then an unstable cervical spine scenario (18 intubations/subject). The specific assigned order of devices and manikins for each participant was based on a three by three Latin square design to minimize carryover effects between the model and the device. Predefined times to intubation were analyzed by Cox regression model and Kaplan–Meier survival curves. Results: Intubation times were shorter and success rates were higher with the Miller blade compared to either the GlideScope or the Truview videoscope in all three manikins in both scenarios, but did not differ between the GlideScope and the Truview devices. Improved intubation times and success rates in the unstable cervical spine scenario compared to the normal neck were attributed to learning effects with sequential intubation. Conclusion: Higher success rates and shorter intubation times with the Miller blade compared to either video‐laryngoscope may reflect greater experience with direct laryngoscopy, need for more video‐laryngoscopy training, or result from the manikin design. Individual practitioners may differ in their preference of device for intubating a child with anticipated difficult airway based on their previous experiences, self‐assessment of their skills, and evaluation of the child's airway anatomy. Abstract :